The new administrative landscape- implications of managerialism for administrative law - De Villiers, David Pieter (Centre for Law and Society, 2026)
In the introductory section to Baxter's Administrative Law, the author in an attempt to delineate the field of administrative law stated the following: 'A factor retarding the development of administrative law as a significant discipline has been a lack of agreement as to what "administrative law" is. Most writers commence with the statement that "administrative law is the law relating to the administration". This is, of course, a safe but useless tautology. Disagreement begins the moment one attempts further amplification. ' 1 This disagreement has not precluded academic writers or the courts from developing this broad1 if difficult to define, body of law. Yet. there remains a high level of uncertainty about the exact scope of administrative law. One might think that asking the question; 'What is considered to be an administrative act or an administrative action?' would remedy this problem to a degree. Again Baxter is opposite: 'The courts have attempted to marshal the wide diversity of administrative acts by grouping them into a set of simple categories .... The labels "legislative", "judicial" and "administrative" have been adopted, along with variants such as "semi-" or "quasi-judicial", "purely administrative" and "ministerial". Once an administrative act has been labelled, the legal rules and principles applicable to it are supposedly clear. But the scheme of classification which has been adopted is in truth simplistic and misleading.